A bug's life [videorecording (DVD)] - Lasseter, John; Stanton, Andrew; Foley, Dave, 1963-; Spacey, Kevin; Louis-Dreyfus, Julia (Disney/Pixar : Distributed by Buena Vista Home Entertainment, 2003)
Journey inside the miniature world of bugs where an ant named Flik hires warrior bugs to defend his colony from a horde of freeloading grasshoppers. Bonus title at end: Geri's game (Academy Award, Best Animated Short, 1997).